THE INFLUENCE OF HALAL AND CONVENTIONAL TOURISM ON NTB'S REGIONAL ORIGINAL REVENUE: A COMPARATIVE ANALYSIS - Siti Maryama; Lukman Insan Kamil; Berlianingsih Kusumawati; Ermalina Ermalina; Amir Hamzah (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: The purpose of this study was to determine the comparison of the effects of conventional tourism and halal tourism on regional original revenue, especially in West Nusa Tenggara (NTB) Province. Design/methodology/approach: This research is a quantitative descriptive research using the ANN (Artificial Neural Network) model. Findings: The results of this study indicate the difference between before becoming halal tourism (conventional) before the NTB governor's regulation, which significantly affects regional original revenue, domestic tourists with a value of 54.68% and foreign tourists with a value of 32.48%, and when it has become halal tourism, which greatly affects foreign tourists, namely (53.52%), and local tourists with a value of 42.91%. As for the USD exchange rate factor against the rupiah, it has no effect on regional original revenue with a value of both 12.82% for conventional tourism and 3.55% for halal tourism. Practical implications: These results are expected to provide input to NTB provincial stakeholders, especially in the field of tourism, to improve and maintain the advantages and uniqueness of halal tourism. Originality/value: Research that compares the effect of tourism before and after becoming halal on regional income is still very rarely done, especially by using the ANN method.